Scent of a woman - Pacino, Al, 1940-; O'Donnell, Chris; Brest, Martin; Universal Pictures (Firm); City Light Films (Universal City, CA : Universal Home Video, 1993)
Hoping to earn extra money, an innocent and reserved scholarship student at an exclusive prep school agrees to look after a blind, retired Lieutenant Colonel, who takes him off for a wild weekend in New York City.
Originally released as motion picture in 1992.
Music, Thomas Newman ; editors, William Steinkamp, Michael Tronick ; production designer, Angelo Graham ; director of photography, Donald E. Thorin.
Al Pacino, Chris O'Donnell, James Rebhorn, Gabrielle Anwar.
MPAA rating: R.
DVD ; Dolby digital.
English, Spanish, and French audio tracks ; captions/subtitles in English and Spanish.
Keywords: Older blind people -- United States -- Drama; Suicidal behavior -- United States -- Drama; Ciegos -- Estados Unidos -- Teatro; Older blind people; Suicidal behavior; United States; Feature films; Films for the hearing impaired; Drama; Feature films; Films -- for the hearing impaired